Logic as a liberal art : an introduction to rhetoric & reasoning - Houser, R. E. (The Catholic University of America Press, 2020)
"This textbook for a first course in logic takes a verbal rather than symbolic approach, based on the student's natural language. It starts by discussing grammar, rhetoric, and the essential nature of logic; formal logic is then taken up following Aristotle's division of the three acts of the mind"--